AB186. The efficacy and safety of sorafenib in Chinese patients with metastatic renal cell carcinoma and prognostic factors related to its efficacy - Yu, Xiaoteng (Transl Androl Urol, 2015)
OBJECTIVE: Sorafenib has been recommended as first- or second-line treatment for metastatic renal cell carcinoma (mRCC) by several guidelines. The objective of this study is to evaluate the efficacy of Sorafenib treatments on Chinese patients with mRCC. METHODS: The characteristics and outcomes of 140 mRCC patients treated with sorafenib monotherapy from two large-volume Chinese centers were retrospectively reviewed to evaluate the long-term efficacy and safety of sorafenib in Chinese patients and identify the prognostic factors associated with response to sorafenib. The primary end-point was overall survival (OS), and the secondary end-points included progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and safety. RESULTS: The median follow-up time was 32 months. The median OS and PFS were 24 months (range, 3-88 months) and 16 months (range, 0-88 months), respectively. Kaplan-Meier and Log rank analyses revealed that patients with clear cell carcinoma had a greater OS (P=0.001) while sarcomatoid differentiation (P=0.045) and disease progression (P=0.010) negatively impacted OS. Furthermore, efficacy analysis revealed that 3 (2.1%) patients achieved complete responses, 28 (20.0%) patients experienced partial responses, 88 (62.9%) patients had stable disease, and 21 (15.0%) patients developed progressive disease. Moreover, the ORR was 22.1%, and the DCR was 85.0%. Most adverse events were classified as grades 1 or 2 with only 14 (10.0%) patients experiencing severe adverse effects (grade 3). CONCLUSIONS: Sorafenib monotherapy can achieve promising OS and PFS for Chinese patients with mRCC, especially in those with clear cell carcinoma, with manageable adverse effect events.